Dealing with English Medium Instruction Factors in Universities - Eva Fatimah; Ahmad Husain; Yuvita Yuvita; Imas Istiani (Dinasti International Journal of Education Management And Social Science, 2024)
This research aims to explore and deal with the factors and perception of English Medium Instrcution Issues around the universities. Quantitative research was chosen by the researcher to find the exact relationship among the factors of English Medium Instruction. The population of the research is the students of Universitas Wahid Hasyim, Universitas Pancasakti Tegal, and Universitas Negeri Semarang, who has recently use English Medium Instruction in their classes. Moreover, the research also reaches the lecturer's voice of English Medium Instruction. The sample was chosen by random sampling method therefore 70 participants participated in this research. The data was tested by a Multiple linear regression test. The result shows if English language skill, motivation, and material understanding has been influencing English Medium Instruction